Dana Alokasi Umum (DAU) dan Pendapatan Asli Daerah (PAD) dalam memprediksi Pertumbuhan Belanja Daerah - Agus Triwanto; Arisyahidin Arisyahidin; Nisa Mutiara (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
Financial management is closely related to the implementation of government affairs through the implementation of decentralization, certain government functions are delegated to regional governments with the aim of increasing added value in the administration of government. In general, the Regional Revenue and Expenditure Budget (APBD) of an area is dominated by central government funds regulated by legislation. This causes regions to be very dependent on the central government. In terms of the influence of General Allocation Fund (DAU) and Local Revenue (PAD) on regional expenditure, the coefficient value of -1.350 has a significant effect on regional expenditure. This shows that regional expenditure in Kediri Regency has a negative relationship with the change in of General Allocation Fund (DAU). In other words, during the period under study, by keeping other variables constant, a 1 percent increase in of General Allocation Fund (DAU) will result in a decrease in regional expenditure of 1,350 percent. And with a coefficient of 4.393 it has a significant effect on regional expenditure. This shows that regional expenditure in Kediri Regency has a positive relationship with changes in Local Revenue (PAD). In other words, during the period under study, by keeping other variables constant, a 1 percent increase in Local Revenue (PAD) would result in an increase in regional expenditure of 4,939 percent. In terms of the effect of of General Allocation Fund (DAU) growth and PAD growth on regional expenditure growth, the coefficient value is -0.884 has a significant effect on the growth of regional spending. This shows that regional expenditure growth in Kediri Regency has a negative relationship with the changing of General Allocation Fund (DAU) growth. In other words, during the period under study, by keeping other variables fixed, a 1 percent increase in of General Allocation Fund (DAU) growth will result in a decrease in regional expenditure growth of 0.884 percent. And with a coefficient value of 0.302 it has no significant effect on regional expenditure growth. This shows that the growth of spending in Kediri Regency has a positive relationship with changes in Local Revenue (PAD) growth. In other words, the increase in Local Revenue (PAD)growth will result in an increase in regional expenditure growth of 0.302 percent.